Ruggedness of Dual-GCT against dynamic avalanche and surge current. (March 2021) - Yang, Wuhua; Wang, Cailin; Yang, Jing; Zhang, Qi; Su, Le
Abstract: Based on multi-cell structure model, the ruggedness of Dual Gate Commutated Thyristor (Dual GCT) against dynamic avalanche and surge current is examined by the device simulation. The simulation results of turn-off behavior show at smaller turn-off delay time, the current filament caused by dynamic avalanche arises in the GCT-A part, which is adverse for the device, and at larger turn-off delay time, the filament arises in the GCT-B part. And the carrier lifetime in the GCT-B part can also influence where the filament appears. Increasing the carrier lifetime of GCT-B part could improve the surge ruggedness of the device, but a compromise must be made between the turn-off and the surge ruggedness. Choosing the lifetime control process that can maximize the temperature dependency coefficient of the lifetime is proved to be an effective method to improve the surge ruggedness while ensuring the turn-off behavior well. Finally, a new Dual GCT structure with proper layout of anode short regions in the GCT-B part is proposed and it is validated by simulation to have excellent surge ruggedness. Highlights: Ruggedness of Dual-GCT against dynamic avalanche and surge current is studied. Turn-off delay time and carrier lifetime distribution can affect filament behavior. Recombination center with higher temperature dependence is favorable for the surge. Novel anode short Dual GCT with excellent surge ruggedness is proposed.